Development of Stirling-type pulse tube cryocooler. (April 2019) - Hong, Yong-Ju; Ko, Junseok; Kim, Hyo-Bong; Yeom, Han-Kil; In, Sehwan; Park, Seong-Je
Abstract: Stirling type pulse tube cryocoolers are very attractive for cooling of diverse application because it has it has several inherent advantages such as no moving part in the cold end, low manufacturing cost and long operation life. A moving magnet type linear motor of dual piston configuration is designed, and this compressor could be operated with the electric power of 100 W at the operating frequency of 50 Hz. A pulse tube cold finger with a double segmented inertance tube was designed for the desired cooling capacity. The coiled inertance tube was assembled inside the reservoir. In experiment, the pulse tube cryocooler is capable of providing the cooling capacity of 2.0 W at 80 K with power consumption of 99.1 W. Random and sinusoidal vibration tests have been conducted to evaluate their performance characteristics and structural integrity.